Stephanocha nom. nov., a replacement name for the illegitimate silicoflagellate genus Distephanus (Dictyochophyceae) - Jordan, Richard; Mccartney, Kevin (Phytotaxa, 2015)
Stephanocha nom. nov. (Silicoflagellata, Dictyochophyceae) is herein proposed as a replacement name for the illegitimate genus name Distephanus, which is a later homonym of Distephanus, a flowering plant. The old generic description is emended, with S. rotunda as the designated type, and new combinations are made for all bona fide silicoflagellate taxa previously assigned (including those tentatively assigned) to Distephanus, except most already transferred to Distephanopsis.